Serbia between Multiethnicity and Multiculturality - Snežana Ilić (Migracijske i Etniĉke Teme, 2009)
The paper researches the possibilities and limitations of theoretical reception and practical applications of policies of multicultural citizenry in today’s Serbia. Diverse comprehensions of authors such as Kymlicka, Loszonc, Schoepflin, Smith, Cilevičs and Barry confront the real state of interethnic relations in East Europe and especially in Serbia. The analysis particularly stresses the question of the living of parallel lives by the members of different national communities instead of their intercultural permeation, as well as advocated solutions in the form of autonomous rights for national minorities and the complex question of the benefit and detriment caused by possible establishment of minority territorial autonomies. The particular position of national minorities in Serbia is largely determined by burdens of its recent past. The author particularly underlines the limitations of elites theories in explanations and practical regulations of interethnic relations, while she affirms the idea of multicultural citizenry as a counter-attitude. As for the national minorities in Serbia, she concludes that education in the mother tongue contributes to the survival of national minorities, while only the widespread and official use of minority languages in a local community enables consistency in the multicultural character of the community itself. Members of national minorities in Serbia live and persist in their group identity in a significantly wider geographical area than the one made up of real multicultural communities. Observed from the point of view determined by Kymlicka’s definition of societal culture as a territorially oriented culture concentrated around common language used privately and publicly, significant ethnically-mixed parts of Serbia i.e. those parts where minorities exist in a considerable, but not dominant number, remain deprived of multiculturality.